2015
DOI: 10.1111/zph.12212
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Value of Passive Animal Health Surveillance: The Case of Highly Pathogenic Avian Influenza in Vietnam

Abstract: SummaryEconomic evaluations are critical for the assessment of the efficiency and sustainability of animal health surveillance systems and the improvement of their efficiency. Methods identifying and quantifying costs and benefits incurred by public and private actors of passive surveillance systems (i.e. actors of veterinary authorities and private actors who may report clinical signs) are needed. This study presents the evaluation of perceived costs and benefits of highly pathogenic avian influenza (HPAI) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 27 publications
0
43
0
1
Order By: Relevance
“…However, because it relies heavily on reports from veterinarians who receive little incentive for reporting, the data reported is frequently incomplete and delayed. Underreporting of disease suspicions is also known to be a major cause of disease control failure (FAO, 2011) and multiple studies have been conducted to better comprehend the decisionmaking processes behind underreporting so as to develop recommendations for improved passive surveillance (Bronner et al, 2014;Delabouglise et al, 2016;Paul et al, 2013;Sawford et al, 2012;Thompson et al, 2016). In contrast, active surveillance demands more time and resources and is thus less commonly employed.…”
Section: Introductionmentioning
confidence: 99%
“…However, because it relies heavily on reports from veterinarians who receive little incentive for reporting, the data reported is frequently incomplete and delayed. Underreporting of disease suspicions is also known to be a major cause of disease control failure (FAO, 2011) and multiple studies have been conducted to better comprehend the decisionmaking processes behind underreporting so as to develop recommendations for improved passive surveillance (Bronner et al, 2014;Delabouglise et al, 2016;Paul et al, 2013;Sawford et al, 2012;Thompson et al, 2016). In contrast, active surveillance demands more time and resources and is thus less commonly employed.…”
Section: Introductionmentioning
confidence: 99%
“…These results highlight the importance of trade-based disease transmission and modulation of the timing of sale -two real features of smallholder livestock systems – on the epidemiological-economic equilibria of avian influenza circulating in a network of profit-maximizing farmers. Results of a sociological survey in Vietnam suggest that fast depopulation is one of the behavioral responses of farmers to HPAI, as respondents reported an increase in poultry sales during epidemic periods (15). The economic context of poultry farming in some endemic countries is favorable to depopulation in response to disease infection: chick and finished poultry are traded with limited equipment (motorcycle for transportation, storage of poultry at home or in enclosures of live bird markets) (29–31) which limits transaction costs associated with the sale and replacement of flocks.…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergence and global spread of the H5N1 subtype of HPAI in 2003, interventions have mainly focused on strengthening avian disease surveillance, preventive culling of domestic birds in outbreak areas, and restrictions on poultry trade; in addition, Vietnam and China implemented mandatory poultry vaccination programs (13, 14). A socio-economic field study conducted in Vietnam showed that farmers fear HPAI detection by the surveillance system not so much because of the risk of mandatory culling but because of its adverse effect on the sale price of poultry (15).…”
Section: Introductionmentioning
confidence: 99%
“…Informal information networks get more and more recognition by public stakeholders and can significantly contribute to surveillance efficiency (Davies, ). In the commercial farming systems in Vietnam, it was found that information networks beyond the village scale were mainly mediated by private suppliers of veterinary services (such as veterinary shops, agro‐industrial companies, feed sellers) (Delabouglise et al., ). In the case of native chicken farmers of Thailand presented hereby, the developed networks are related to a recreational activity.…”
Section: Discussionmentioning
confidence: 99%